Narrownose smoothhound (Mustelus schmitti) shark liver: From a residue to a high added value biocompounds - Lamas, Daniela Lorena (2024)
The exploration of fishery wastes for the extraction of value-added biocompounds has become a topic of current interest. The aim of this work was to promote a circular economy model by obtaining oil by enzymatic hydrolysis from Mustelus schmitti livers and incorporating it into bread. The oil extraction reaction was carried out using Alcalase® 2.4 L at pH 8.0, 55 ◦C of temperature for 60 min. Fatty acid analysis showed that the oil was rich in ω-3 long chain fatty acids (LCω3PUFAs), with the eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) being the main constituents (13 and 70 % of total PUFAs, respectively). Then, an external gelation method was developed to produce alginate capsulates loaded with the extracted oil. The encapsulation efficiency (EE) was 93.41 %. Finally, capsulated and unencapsulated fish oil were used to develop breads and more than 95 % of EPA and DHA were recovered after baking. Thus, 20 g of baked product can provide about 45 % of the recommended minimum daily intake of EPA plus DHA. The results suggest that it is possible to use the liver from the narrownose smoothhound (Mustelus schmitti) shark fishery to produce value-added products based on a circular economy.